2019
DOI: 10.1002/ejhf.1350
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for incident heart failure in age‐ and sex‐specific strata: a population‐based cohort using linked electronic health records

Abstract: Aims Several risk factors for incident heart failure (HF) have been previously identified, however large electronic health records (EHR) datasets may provide the opportunity to examine the consistency of risk factors across different subgroups from the general population. Methods and results We used linked EHR data from 2000 to 2010 as part of the UK‐based CALIBER resource to select a cohort of 871 687 individuals 55 years or older and free of HF at baseline. The primary endpoint was the first record of HF fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 37 publications
(57 reference statements)
1
60
0
2
Order By: Relevance
“…The majority of phenotyping algorithms were created to ascertain disease status (n=54) (e.g. heart failure [Gho et al 2018;Uijl et al 2019], depression [Daskalopoulou et al 2016]), ten algorithms were created to extract information on biomarkers (e.g. heart rate [Archangelidi et al 2018], blood pressure [Rapsomaniki et al 2014]) and six algorithms were used to identify lifestyle risk factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of phenotyping algorithms were created to ascertain disease status (n=54) (e.g. heart failure [Gho et al 2018;Uijl et al 2019], depression [Daskalopoulou et al 2016]), ten algorithms were created to extract information on biomarkers (e.g. heart rate [Archangelidi et al 2018], blood pressure [Rapsomaniki et al 2014]) and six algorithms were used to identify lifestyle risk factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, primary care information for just under half of the cohort (n=230,000) will be made available for UK Biobank researchers in June 2019. Algorithms incorporating primary care data for the conditions already covered have been or are being developed [Wilkinson et al 2019]. Along with a range of additional algorithms expanding the range of health outcomes available, they will be available from UK Biobank later in 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the indirect effects of family history of CVD, age, lipid pro les, anthropometric indices, healthy lifestyle, quality of life, high-risk behaviours, having hypertension and high blood sugar on CVDs were not covered in the literature, many studies discussed the direct effect of such factors in which these results are in line with (9,11,12,15,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Causal networks evaluate causal relationships among variables beyond partial correlations and thus play a fundamental step in risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular (CV) risk factors and co-morbidities are major determinants of HF phenotypes. 3 Uijl et al 4 reported the association between them and incident HF in a large cohort of 871 687 subjects stratified by gender and age. Modifiable risk factors (social deprivation, smoking, sedentary lifestyle, body mass index) and co-morbidities (diabetes, AF, chronic obstructive pulmonary disease, renal insufficiency) were associated with incident HF.…”
Section: Risk Factors and Preventionmentioning
confidence: 99%